Preparation Of Competent Human Resources For The Industrial Revolution 4.0 - Suwandi, Suwandi (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The Industrial Revolution 4.0 has occurred since 2011 at the Hannover Fair in Germany, where it has received high attention from scholars. Although Industry 4.0 originated in Germany, internationally it has become a motivation and guide for humans. The country’s manufacturing industry. The adoption of new technology greatly affects several parties, such as employees who carry out daily activities in the Industry, as well as influencing the Organization so that it can realize its full potential and adopt flexible strategic decision-making and problem- solving roles. With the Industrial Revolution 4.0, it is hoped that Human Resource Management must adapt to change. The Industrial Revolution is the most profound revolution in human history because of its far-reaching impact on the daily life of people. The mission of Transdisciplinary Education and Learning is to create a learning community, accommodate lifelong learning, competency-based learning, transdisciplinary, education systems and transdisciplinary learning are designed and implemented using system management. Continuous development of practical competencies, basic competencies and reflective competencies will provide an increase in practice standards so that they develop from minimum competency standards to higher competency standards, also known as having capabilities.